2014
DOI: 10.1128/jcm.00035-14
|View full text |Cite
|
Sign up to set email alerts
|

Airway Microbiome Dynamics in Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Specific bacterial species are implicated in the pathogenesis of exacerbations of chronic obstructive pulmonary disease (COPD).However, recent studies of clinically stable COPD patients have demonstrated a greater diversity of airway microbiota, whose role in acute exacerbations is unclear. In this study, temporal changes in the airway microbiome before, at the onset of, and after an acute exacerbation were examined in 60 sputum samples collected from subjects enrolled in a longitudinal study of bacterial infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
252
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(275 citation statements)
references
References 44 publications
(62 reference statements)
18
252
2
3
Order By: Relevance
“…In agreement with HUANG et al [8], we found a decreased microbial α diversity with an increase of Proteobacteria over Firmicutes in subjects treated with corticosteroids alone (figure 4). At the genus level, this corresponded to a decrease of Streptococcus and an increase of Haemophilus and Moraxella.…”
Section: Oral Corticosteroids and Antibiotics Have Different Effects supporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with HUANG et al [8], we found a decreased microbial α diversity with an increase of Proteobacteria over Firmicutes in subjects treated with corticosteroids alone (figure 4). At the genus level, this corresponded to a decrease of Streptococcus and an increase of Haemophilus and Moraxella.…”
Section: Oral Corticosteroids and Antibiotics Have Different Effects supporting
confidence: 93%
“…The genera Streptococcus (prevalence 95.0%), Haemophilus (94.7%), Rothia (94.1%), Veillonella (93.2%) and Prevotella (90.3%) were highly prevalent across all visits (table 3). There was a significantly greater inter-subject variation in microbiome community at the same visit (weighted UniFrac±SD 0.387±0.186) compared with temporal variation within each subject (weighted UniFrac±SD 0.272±0.181, p=2.2e−16 using t-test), suggesting that for our cohort the lung microbiome was relatively stable over time [8].…”
Section: Lung Microbiome Profilesmentioning
confidence: 70%
See 2 more Smart Citations
“…De nombreuses pistes ont été décrites pour expliquer comment l'exposition tabagique détruit les défenses pulmonaires de l'hôte via la suppression de la production de peptides antimicrobiens, la destruction de la barrière épithéliale et la colonisation des voies aériennes inférieures par un certain nombre d'agents microbiologiques [25,30,31] [33]. Le microbiote est également modifié par l'antibiothérapie et la corticothérapie [24]. Il est également différent chez les patients atteints de mucoviscidose.…”
Section: Microbiome Pulmonaire Et Broncho-pneumopathie Chronique Obstunclassified